2021
DOI: 10.1038/s41419-021-04118-4
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase 1 promotes gemcitabine resistance by regulating the PVT1/EZH2 complex in pancreatic cancer

Abstract: The poor prognosis of pancreatic cancer is primarily due to the development of resistance to therapies, including gemcitabine. The long noncoding RNA PVT1 (lncRNA PVT1) has been shown to interact with enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), promoting gemcitabine resistance in pancreatic cancer. In this study, we found histone acetyltransferase 1 (HAT1) enhanced the tolerance of pancreatic cancer cells to gemcitabine and HAT1-mediated resistance mechanisms were regulated by PVT1 and EZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…To govern cell adhesion in human cells, pRB and UBR4 interact directly and co-localize in the nucleus [ 24 ]. UBR4 is a UBR box E3 ligase that uses the N-degron pathway to degrade proteins [ 24 , 25 , 26 , 27 ]. Sequence similarity analysis reveals that BIG has the conserved UBR box and E3 ligase domains ( Figure S2A ), pointing to a scenario that BIG might also regulate RBR levels through the N-degron pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To govern cell adhesion in human cells, pRB and UBR4 interact directly and co-localize in the nucleus [ 24 ]. UBR4 is a UBR box E3 ligase that uses the N-degron pathway to degrade proteins [ 24 , 25 , 26 , 27 ]. Sequence similarity analysis reveals that BIG has the conserved UBR box and E3 ligase domains ( Figure S2A ), pointing to a scenario that BIG might also regulate RBR levels through the N-degron pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin protein ligase E3 component N-recognin 4 (UBR4) is a 600-kDa calmodulin-interacting protein involved in the N-end rule pathway [ 24 , 25 , 26 , 27 ]. BIG was originally identified in a mutational screen for resistance against N-1-naphthylphthalamic acid (NPA), a potent auxin transport inhibitor [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Sun et al. [ 115 ] showed that HAT1 improves the resistance of PC to chemotherapy by promoting PVT1 expression and inhibiting EZH2 degradation. Moreover, You et al.…”
Section: Role Of Pvt1 In Various Human Tumorsmentioning
confidence: 99%
“…1C) [56]. Wan et al [42] demonstrated that PVT1 repressed the expression of LAST2 by recruiting EZH2 to the Pancreatic cancer Upregulation Oncogene Progression and glycolysis miR-519d-3p HIF-1A [111] Pancreatic cancer Upregulation Oncogene Autophagy miR-20a-5p ULK1 [113] Pancreatic cancer Upregulation Oncogene Chemoresistance / EZH2 [115] Pancreatic cancer Upregulation Oncogene Proliferation miR-1207 / [116] Pancreatic cancer Upregulation Oncogene Chemoresistance miR-409 SHH/GLI/MGMT [117] Pancreatic cancer Upregulation Oncogene Chemoresistance miR-619-5p Pygo2 [118] promoter region of LAST2. LAST2 is an upstream phosphokinase of the Hippo signaling pathway that can phosphorylate YAP1 to reduce its expression and activate the Hippo signaling pathway.…”
Section: Pvt1 In Non-small Cell Lung Cancermentioning
confidence: 99%
“…Simultaneously, HAT1 competitively binds to the N-terminus of EZH2 with the ubiquitin protein ligase E3 component n-recognin 4 (UBR4), preventing the ubiquitination of EZH2. Thus, HAT1 promotes gemcitabine resistance in pancreatic cancer cells (28). Based on this mechanism, tripolyphosphate (TPP)-siHAT1 nanoparticles have been developed to inhibit HAT1 expression and overcome gemcitabine resistance in pancreatic cancer cells.…”
Section: Pancreatic Cancermentioning
confidence: 99%